If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1t + 4 = 13 Reorder the terms: 4 + -1t = 13 Solving 4 + -1t = 13 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1t = 13 + -4 Combine like terms: 4 + -4 = 0 0 + -1t = 13 + -4 -1t = 13 + -4 Combine like terms: 13 + -4 = 9 -1t = 9 Divide each side by '-1'. t = -9 Simplifying t = -9
| 4a+5=35 | | 5ln(x+4)-17=8 | | 12ab+6ab-9bc= | | 3x-16=4-2x | | 48s-34=48-28s | | 10-7=63 | | 51x-7=34x+163 | | .06x+x=5000 | | 3(4x)=27 | | 35-10= | | (x+5)(x+7)=105 | | sin(2x)=cos(5x) | | b^2-3=6 | | Y=9x-4xy+2x-xy | | 5r^2=10 | | 4y+20=15y-24 | | 3*ln(x+2)=9 | | 112+13p=86 | | 5x-16=x | | 5y-7=y+3 | | 4x-18=17+5 | | 56-6x=-28+8x | | 2x^2+8x-26=0 | | 5q^3(q^4-6q)= | | 96x+51y=6 | | ((6n^3)/(7x^5*y^2))/((3mn^20/(21x^3*y)) | | n/3=2n/6 | | 2x^2+4y=6 | | -2a+5a-12a= | | 5g-9-g=3G+12 | | 3(2p-1)=4p-11 | | 5/12x-12=48 |